High-Throughput Native Mass Spectrometry Screening in Drug Discovery - Gavriilidou, Agni F. M.; Sokratous, Kleitos; Yen, Hsin-Yung; De Colibus, Luigi (Frontiers in Molecular Biosciences, 2022)
The design of new therapeutic molecules can be significantly informed by studying protein-ligand interactions using biophysical approaches directly after purification of the protein-ligand complex. Well-established techniques utilized in drug discovery include isothermal titration calorimetry, surface plasmon resonance, nuclear magnetic resonance spectroscopy, and structure-based drug discovery which mainly rely on protein crystallography and, more recently, cryo-electron microscopy. Protein-ligand complexes are dynamic, heterogeneous, and challenging systems that are best studied with several complementary techniques. Native mass spectrometry (MS) is a versatile method used to study proteins and their non-covalently driven assemblies in a native-like folded state, providing information on binding thermodynamics and stoichiometry as well as insights on ternary and quaternary protein structure. Here, we discuss the basic principles of native mass spectrometry, the field’s recent progress, how native MS is integrated into a drug discovery pipeline, and its future developments in drug discovery.